Autophagy in intracellular bacterial infection. (May 2020) - Hu, Wei; Chan, Hung; Lu, Lan; Wong, Kam Tak; Wong, Sunny H.; Li, Ming X.; Xiao, Zhan G.; Cho, Chi H.; Gin, Tony; Chan, Matthew T.V.; Wu, William K.K.; Zhang, Lin
Abstract: Autophagy is a conserved intracellular degradation process enclosing the bulk of cytosolic components for lysosomal degradation to maintain cellular homeostasis. Accumulating evidences showed that a specialized form of autophagy, known as xenophagy, could serve as an innate immune response to defend against pathogens invading inside the host cells. Correspondingly, infectious pathogens have developed a variety of strategies to disarm xenophagy, leading to a prolonged and persistent intracellular colonization. In this review, we first summarize the current knowledge about the general mechanisms of intracellular bacterial infections and xenophagy. We then focus on the ongoing battle between these two processes.